AIJSS 2020
DOI: 10.30845/aijss.v9n2p1
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement Model of Depressive Symptoms among Older, African American Women

Abstract: For more than four decades, researchers have found depression to be a common mental illness among the elderly. Depression is a generalized mood disorder characterized by feelings of sadness and hopelessness, a sense of worthlessness, difficulty concentrating, loss of interest, and decrease in energy level. This definition is reflected in the Geriatric Depression Scale (GDS). The rates of depression among elderly residents of institutions are 67% higher than among elderly adults residing at home. As in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(52 reference statements)
1
0
0
Order By: Relevance
“…In the present study, depression and stress were significantly higher among those who reported being unmarried and with a lower number of family members. Being alone during lockdown can often cause feelings of loneliness and affect mental well-being leading to depression and stress ( 49 , 50 ), and the present study supports and such findings. A previous study has reported that being married (compared to being single, widowed or separated) can be associated with depression ( 51 ), however this utilized data collected prior to the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, depression and stress were significantly higher among those who reported being unmarried and with a lower number of family members. Being alone during lockdown can often cause feelings of loneliness and affect mental well-being leading to depression and stress ( 49 , 50 ), and the present study supports and such findings. A previous study has reported that being married (compared to being single, widowed or separated) can be associated with depression ( 51 ), however this utilized data collected prior to the pandemic.…”
Section: Discussionsupporting
confidence: 87%